2013
DOI: 10.1371/journal.pone.0054226
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy Prediction in Single Embryo Transfer Cycles after ICSI Using QPCR: Validation in Oocytes from the Same Cohort

Abstract: Cumulus cell (CC) gene expression is being explored as an additional method to morphological scoring to choose the embryo with the highest chance to pregnancy. In 47 ICSI patients with single embryo transfer (SET), from which individual CC samples had been stored, 12 genes using QPCR were retrospectively analyzed. The CC samples were at the same occasion also used to validate a previously obtained pregnancy prediction model comprising three genes (ephrin-B2 (EFNB2), calcium/calmodulin-dependent protein kinase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 38 publications
1
30
0
Order By: Relevance
“…However, the apparent inconsistency between the present study and the study by Haouzi et al [ 5 ] could be explained by the different study designs and experimental approaches: Firstly, we used enzymatically isolated CRCs, which constitute the innermost cells closest to the oocyte, whereas Haouzi et al [ 5 ] used mechanically cut cumulus cells. Several previous studies have successfully used enzymatically isolated cumulus cells [ 24 29 ] and CRCs [ 30 , 31 ] to investigate gene expression differences according to e.g. oocyte quality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the apparent inconsistency between the present study and the study by Haouzi et al [ 5 ] could be explained by the different study designs and experimental approaches: Firstly, we used enzymatically isolated CRCs, which constitute the innermost cells closest to the oocyte, whereas Haouzi et al [ 5 ] used mechanically cut cumulus cells. Several previous studies have successfully used enzymatically isolated cumulus cells [ 24 29 ] and CRCs [ 30 , 31 ] to investigate gene expression differences according to e.g. oocyte quality.…”
Section: Discussionmentioning
confidence: 99%
“…The strict use of CRCs from MІІ oocytes developing into top quality embryos in the present microarray study might explain why there were no individual genes with significant differential expression between PCOS and controls. Previous studies have shown that the transcriptome of cumulus cells from MІІ oocytes of poor developmental competence differed from cumulus cells of MІІ oocytes with high developmental competence [ 24 , 26 , 29 , 31 36 ]. These previous findings underlined the importance of oocyte selection, when comparing cumulus cells or CRCs in relation to a certain condition, such as PCOS.…”
Section: Discussionmentioning
confidence: 99%
“…Additional cumulus cell genes involving signaling, homeostasis, and metabolism have been variably reported as higher (VCAN, PTGS2, EFNB2, SPSB2, UBQLN1, DPP8, HIST1H4C, CALM1, NRP1, PSMD6, BCL2L11, PCK1, and RGS2) or lower (TOM1, NFIB) in association with embryos yielding pregnancy or live births compared with embryos failing to implant (110)(111)(112)(113)(114)(115)(116). In addition, cumulus cell gene expression of HAS2 and FSH receptor has been used to select up to three metaphase II oocytes within a cohort of oocytes, from which one selected oocyte (vs. a randomly selected metaphase II oocyte) has a 60% (vs. a 38%) chance of developing to a live birth (111).…”
Section: Cellular Markers Of Oocyte Competencementioning
confidence: 99%
“…Exploring a different concept and introducing the value of the genetic factor in model development, Wathlet et al (2013) folded 'genomics' into a prediction model on a successful embryo transfer and live birth. They initially compared the RNA levels of 12 genes derived from cumulus cells of pregnant and non-pregnant women.…”
Section: Biomarkers Of the Embryo As Prognostic Indicators Of Successmentioning
confidence: 99%